The Comparison of Different Irrigation Systems to Remove Calcium Hydroxide from the Root Canal: A Systematic Review and Meta-Analysis - Samira Jamali; Golchin Jabbari; Elnaz Mousavi; Hashem Ahmadizadeh; Mohammad Khorram; Azad Jamee (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To examine the effect of a variety of irrigation systems on the removal of root canal Ca (OH)2 residues through meta-analysis and systematic review. Material and Methods: A search of relevant articles was systematically performed on databases of Medline, PubMed, Cochrane Library, Embase, ISI, and Google Scholar published from 2013 to 2019. Electronic title management was carried out by EndNote X9 software. Searches were based on the main keywords of “Irrigation Systems”, “Calcium Hydroxide”,” Root Canal”, “Self-adjusting File OR SAF”, “Conventional Irrigation”, “EndoVac System”, “Ultrasonic Irrigation” and “YAG Laser”. Results: The studies investigated were found to lack any standardization concerning the irrigation method used or the measurement of outcomes; for instance, different studies used 5 or 10 mL of 2.5% NaOCl, or 5 mL of 5.25% NaOCl, or 0.5 mL, 3 mL and 10 mL of 17% EDTA. Conclusion: The effective techniques for the removal of root canal Ca(OH)2 were PUI, and SAF approaches.